THE EFFECT OF LEARNING APPROACH AND READING INTEREST TOWARD STUDENTS NARRATIVE WRITING ACHIEVEMENT - Noldy Pelenkahu (Soegijapranata Catholic University, 2014)
The aim of this research is to know the different kinds of instructional approaches (process skill and goals oriented) found in the process of learning narrative writing. The use of different instructional approaches gave different results on students achievement in narrative writing. Students who have different reading interests also showed different achievement in narrative writing. These two variables have a relationship in implementing instructional approach and reading interest. It showed that the testing result of interaction between the variables of process skill and goals oriented instructional approaches to narrative writing achievement is possible. It can be concluded that the use of different instructional approach (process skill and goals oriented) give different final results. The same result is also done to students who have different reading interests as they will give different narrative writing achievements.